1996
DOI: 10.1074/jbc.271.32.19037
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Muscle Sodium Channels by Intracellular Fatty Acids Is Dependent on the Channel Isoform

Abstract: Free fatty acids (FFAs), including arachidonic acid (AA), are implicated in the direct and indirect modulation of a spectrum of voltage-gated ion channels. Skeletal muscle sodium channels can be either activated or inhibited by FFA exposure; the response is dependent on both FFA structure and site of exposure. Recombinant human skeletal muscle sodium channels (hSkM1) were transfected into heterologous human renal epithelium HEK293t cells. Cytoplasmic delivery of 5 M AA augmented the voltage-activated sodium cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…h, (Mochizuki-Oda et al, 1993; Asano et al, 1997; Liu et al, 2006; Gutla et al, 2012). i, (Linden and Routtenberg, 1989; Wieland et al, 1992, 1996; Fraser et al, 1993; Charpentier et al, 1995; Kang et al, 1995, 1997; Xiao et al, 1995, 1998, 2000, 2001, 2004, 2005, 2006; Kang and Leaf, 1996; Vreugdenhil et al, 1996; Bendahhou et al, 1997; Fyfe et al, 1997; Macleod et al, 1998; Lee et al, 1999, 2002; Leifert et al, 1999; Ding et al, 2000; Harrell and Stimers, 2002; Leaf et al, 2002; Hong et al, 2004; Jo et al, 2005; Kim et al, 2005; Isbilen et al, 2006; Pignier et al, 2007; Duan et al, 2008; Dujardin et al, 2008; Gu et al, 2009, 2015; Nakajima et al, 2009, 2010; Fang et al, 2011; Guo et al, 2012; Wolkowicz et al, 2014; Safrany-Fark et al, 2015; Wannous et al, 2015). j, (Keyser and Alger, 1990; Finkel et al, 1992; Hallaq et al, 1992; Huang et al, 1992; Shimada and Somlyo, 1992; Damron and Bond, 1993; Dettbarn and Palade, 1993; Pepe et al, 1994; Törnquist et al, 1994; Williams et al, 1994; Roudbaraki et al, 1995; Nagano et al, 1995b; Schmitt and Meves, 1995; van der Zee et al, 1995; Petit-Jacques and Hartzell, 1996; Shimasue et al, 1996; Shuttleworth, 1996; Uehara et al, 1996; Unno et al, 1996; Damron and Summers, 1997; Munaron et al, 1997; Striggow and Ehrlich, 1997; Xiao et al, 1997; Hazama et al, 1998; Chen et al, 1999, 2001; Fang et al, 1999; Liu and...…”
Section: Effects Of Pufa On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…h, (Mochizuki-Oda et al, 1993; Asano et al, 1997; Liu et al, 2006; Gutla et al, 2012). i, (Linden and Routtenberg, 1989; Wieland et al, 1992, 1996; Fraser et al, 1993; Charpentier et al, 1995; Kang et al, 1995, 1997; Xiao et al, 1995, 1998, 2000, 2001, 2004, 2005, 2006; Kang and Leaf, 1996; Vreugdenhil et al, 1996; Bendahhou et al, 1997; Fyfe et al, 1997; Macleod et al, 1998; Lee et al, 1999, 2002; Leifert et al, 1999; Ding et al, 2000; Harrell and Stimers, 2002; Leaf et al, 2002; Hong et al, 2004; Jo et al, 2005; Kim et al, 2005; Isbilen et al, 2006; Pignier et al, 2007; Duan et al, 2008; Dujardin et al, 2008; Gu et al, 2009, 2015; Nakajima et al, 2009, 2010; Fang et al, 2011; Guo et al, 2012; Wolkowicz et al, 2014; Safrany-Fark et al, 2015; Wannous et al, 2015). j, (Keyser and Alger, 1990; Finkel et al, 1992; Hallaq et al, 1992; Huang et al, 1992; Shimada and Somlyo, 1992; Damron and Bond, 1993; Dettbarn and Palade, 1993; Pepe et al, 1994; Törnquist et al, 1994; Williams et al, 1994; Roudbaraki et al, 1995; Nagano et al, 1995b; Schmitt and Meves, 1995; van der Zee et al, 1995; Petit-Jacques and Hartzell, 1996; Shimasue et al, 1996; Shuttleworth, 1996; Uehara et al, 1996; Unno et al, 1996; Damron and Summers, 1997; Munaron et al, 1997; Striggow and Ehrlich, 1997; Xiao et al, 1997; Hazama et al, 1998; Chen et al, 1999, 2001; Fang et al, 1999; Liu and...…”
Section: Effects Of Pufa On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…A study with the hH1(α) Na + channel led to the discovery of the importance of Asn 406 in the inhibition of cardiac voltage-gated Na + currents by PUFA (Xiao et al, 2001). Another study using cells transfected with the skeletal muscle sodium channels (SkM1) isoform showed that ion channel modulation by FFA depends on the mode of FFA administration (Wieland et al, 1996). Intracellular AA exposure increased channel currents whereas the hH1 isoform did not show significant current increases.…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…These results point to the existence of two distinct sites and mechanisms for FFA modulation of sodium channels: a potential extracellular site for extracellular FFA, and an intracellular one that appears to be exclusively for SkM1. The activation effect was observed over 120 min, suggesting that neo-synthesis and trafficking/insertion of new channels to/in the cell membrane could occur during this period, alone or in combination with unmasking of reserve channels already present in the plasmalemma (Wieland et al, 1996). This dual mechanism was also observed in the muscle rNa(V)1.4 channel isoform, which appears to depend on the depolarizing potential: AA, but not its metabolites, increased the channel current evoked by a −30 or −40 mV depolarization of the membrane potential, but significantly decreased it by a depolarization over −10 mV (Gu et al, 2009).…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…30 In cultured rat cardiomyocytes, in vitro treatment with iron altered membrane fatty acids 31 and suppressed mitochondrial respiratory enzymes, with a concomitant reduction in cellular ATP. 32 The decrease in ATP might alter phosphorylation of Na ϩ channel protein, which affects steady-state inactivation and recovery from inactivation.…”
Section: Namentioning
confidence: 99%